4(x-2)/3x+1
is the most simplified i can get
Answer:
False
Step-by-step explanation:
In this question, you roll 3 from the standard die and then add it with the next roll to see if the sums are greater than 4.
From this explanation you can see that you use the result from your first roll for the second event, so we can conclude that the event is dependent.
Imagine if we change the result of the first roll into 5, without adding the second roll we can know that the sum will be greater than 4. The first event result will influence the second event, so it is a dependent event.
Answer: 0.5%
3 pages out of 650 is 0.5%
Step-by-step explanation:
factor 4 out of the variable terms, as this helps.
but my approach is simply to define the target and then calculate "backwards".
we want to find
(ax + b)² = a²x² + 2abx + b²
and now we compare with the original equation :
a²x² = 4x²
a² = 4
a = 2
2abx = 16x
2×2×bx = 16x
4b = 16
b = 4
b² = 16, but we have only 3, so we need to subtract 16-3 = 13 from the completed square.
so, our equation is
(2x + 4)² - 13 = 0
(2x + 4)² = 13
2x + 4 = sqrt(13)
2x = sqrt(13) - 4
x = sqrt(13)/2 - 2
Context ? i need more info.